General principles of systems. Issue 8 (3rd September 2018) - Korn, Janos
Abstract : Purpose: Three problematic issues followed by paradigm changes over the recent history of human intellectual endeavour are identified as 1. mysticism/superstition to – conventional science (of physics), 2. predominant use of qualitative/quantitative properties for analysis and design to – structural or systemic properties, and 3. current speculative/fragmented, multiple approaches to the "systemic view" to – a firmer knowledge-based approach reflecting the empirical and universal nature of this view. This paper aims to consider the problematic issues, to conclude that conventional science is inadequate to cope with the 2nd paradigm change and to introduce a "new science of systems" which can integrate conventional science and alleviate the 3rd problematic issue by suggesting three principles implemented by linguistic modelling as operational model. Design/methodology/approach: The highly successful methodology of conventional science is followed with systemic content by suggesting three general principles of systems, namely, principle of existence (pervasiveness of structural description), principle of complexity (aggregates for emergence of outcomes) and principle of change (change by purpose or chance), and linguistic modelling of static and dynamic scenarios based on natural language as operational model. This language is processed to "elementary constituents", of which complex structures can be constructed. These constituents are converted into reasoning schemes consisting of "ordered pairs" and "predicate logic statements" in static and dynamic states. Findings: Stories of problematic scenarios are converted into the universal scheme of "management/producers" – "products" – "users/consumers" by constructing linguistic networks of products and semantic diagrams of organizations/user/consumers for investigating the emergence of outcomes in analysis and for designing prototypes. Problematic issues of individual objects in a scenario are resolved by methods of conventional science, which is thus integrated with systems science to form the "scientific enterprise". Research limitations/implications: Once the new approach is debated, further developments in the mathematics of ordered pairs, predicate logic and uncertainties are needed. The linguistic basis is to be further investigated. Connection with AI and "logical atomism of Bertrand Russell" is to be explored. Practical implications: Further applications to large-scale scenarios by practitioners using the "universal scheme" and development of software are needed. Social implications: The approach is rooted in accepted branches of knowledge, is highly teachable and should lead to be used by professionals and others once debated and accepted.